Uric acid detection using uv-vis spectrometer - Nor Mazlee, Norazmi; Zul Rasyied, Abdul Rasat; Mazuina, Mohamad; Hadi, Manap (IOP Publishing, 2017)
The aim of this research is to detect uric acid (UA) concentration using Ultraviolet-Visible (UV-Vis) spectrometer in the Ultraviolet (UV) region. Absorption technique was proposed to detect different uric acid concentrations and its UV absorption wavelength. Current practices commonly take a lot of times or require complicated structures for the detection process. By this proposed spectroscopic technique, every concentration can be detected and interpreted into an absorbance value at a constant wavelength peak in the UV region. This is due to the chemical characteristics belong to the uric acid since it has a particular absorption cross-section, σ which can be calculated using Beer’s Lambert law formula. The detection performance was displayed using Spectrasuite sofware. It showed fast time response about 3 seconds. The experiment proved that the concentrations of uric acid were successfully detected using UV-Vis pectrometer at a constant absorption UV wavelength, 294.46 nm in a low time response. Even by an artificial sample of uric acid, it successfully displayed a close value as the ones reported with the use of the medical sample. It is applicable in the medical field and can be implemented in the future for earlier detection of abnormal concentration of uric acid.